(untitled) (SCIÉNDO INGENIUM, 2022)
Bacillus sp. and Pseudomonas sp. they are capable of promoting plant growth and reducing the stress caused by salinity. Given this, the present study sought to determine the potential of Bacillus sp. and Pseudomonas sp. isolated from the rhizosphere of Opuntia quitensis "prickly pear" as growth promoters in Zea mays L. "corn" under saline stress. The sample of roots and rhizospheric soil of prickly pear was carried out and it was taken to the laboratory for the isolation and phenotypic identification of Bacillus sp. and Pseudomonas sp., to subsequently determine their ACC deaminase activity and the ability to increase the germination rate of corn seeds, likewise, the ten bacterial cultures with the best results were quantified indoles, soluble phosphorus and solubilization index. It was found that, of 170 isolated bacteria, 100 correspond to the genus Bacillus sp. and 53 to the genus Pseudomonas sp. Furthermore, 10% of Bacillus sp. and 30.18% of Pseudomonas sp. demonstrated to have ACC deaminase activity, increased the germination rate of corn seeds by 42.30%. Both bacteria showed the ability to produce indoles and solubilize phosphates, showing their potential as growth promoters in plants under saline stress.